Does cultural economics affect country’s competitiveness? - Astikė, Kristina (Business, Management and Economics Engineering, 2022)
Purpose – the purpose of the article is to identify factors of cultural economics and examine their impact on countries’ competitiveness.Research methodology – in this study, the following factors have been determined to affect the competitiveness of the European Union countries: cultural employment by age (18–65), general government expenditure on cultural services, households expenditure on cultural goods, persons working as creative and performing artists, authors, journalists and linguists engaged in individual activity and employment. Panel data, which are processed with the Gretl software, are used for the study.Findings – the results revealed that all the distinguished factors affect the competitiveness of the European Union countries; however, general government expenditure by function has the most significant effect.Research limitations – the article analyses all countries of the European Union except Romania because there is a lack of statistical data on this country, which interferes with the research. Practical implications – as cultural economics is linked to both the public and private sectors, the revenue and the products it generates undoubtedly contribute to the country’s economic development and, hence, competitiveness.Originality/Value – cultural economics is an interdisciplinary field of scientific research described and analysed by various authors as the interaction of human-made activities with new technologies, various artistic forms, knowledge, and creativity. Consequently, cultural economics has received more and more attention. However, the factors of cultural economics and their impact on a country’s competitiveness level is a fragmentarily examined topic which shows its originality.